Sunda-“Java” and The Past : A Socio-Historical Reflection - Fachry Ali (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2016)
This piece directs its attention to the psycho-historical consciousness between two major Indonesia’s ethnic groups: Sunda and Java. The 14th century of Bubat War in Majapahit, East Java and the Central Java Mataram Kingdom’s “occupation” over the Land of Sunda in 16th and 17th centuries had created psychological problem that marked an uneasy relations between both of these ethnic groups, when the nationalism fountainhead is refered to the heyday histories of the East and Central Java’s kingdoms. The Sundanese nationalism finally was flown into modern Indonesian nationalism. By choosing the latest, the Sundanese were freed from the past bitter memories.DOI: 10.15408/insaniyat.v1i1.4350